BoLA‐DRB3 genetic diversity in Highland Creole cattle from Bolivia. (5th November 2020) - Giovambattista, Guillermo; Takeshima, Shin‐Nosuke; Moe, Kyaw Kyaw; Pereira Rico, Juan A.; Polat, Meripet; Loza Vega, Ariel; Arce Cabrera, Orlando N.; Aida, Yoko
Abstract : The genetic diversity of the BoLA‐DRB3 gene has been reported in different cattle breeds owing to its central role in the immune response. However, it is still unknown in hundreds of cattle breeds, especially native populations. Here, we studied BoLA‐DRB3 genetic diversity in Highland Creole cattle (CrAl) from Western Bolivia, raised at altitudes between 3800 and 4200 m. DNAs from 48 CrAl cattle were genotyped for BoLA‐DRB3 exon 2 alleles using polymerase chain reaction‐sequence‐based typing (PCR‐SBT). The results were compared with 1341 previously reported data from Tropical Creole cattle and other breeds raised in the region. Twenty‐three BoLA‐DRB3 alleles were identified in CrAl, including the BoLA‐DRB3*029:02 variant previously detected in other Creole cattle. Observed and expected heterozygosity were 0.87 and 0.93, respectively. Nucleotide diversity and the number of pairwise difference values were 0.078 and 19.46, respectively. The average number of nonsynonymous and synonymous substitutions were 0.037 and 0.097 for the entire BoLA‐DRB3 exon 2, and 0.129 and 0.388 for the antigen‐binding site, respectively. Venn analysis and the review of the IPD‐MHC database and the literature showed that 2 of 64 alleles were only detected in CrAl, including BoLA‐DRB3*029:01 previously reported in African cattle and *048:01 detected in Philippine cattle. Two additional alleles, BoLA‐DRB3*007:02 and *029:02, were only present in CrAl and Lowland Creole cattle. Principal Component Analysis (PCA) showed that Bolivian Creole cattle breeds were closely located but they were distant from the Colombian Hartón del Valle Creole. FST analysis showed a low degree of genetic differentiation between Highland and Lowland Bolivian Creole cattle (FST = 0.015). The present results contribute to increasing our knowledge of BoLA‐DRB3 genetic diversity in cattle breeds.